HUBUNGAN KERAPATAN DAN PANJANG TRIKOMA DAUN PADA KACANG TANAH (Arachis hypogaea L.) TERHADAP PREFERENSI PELETAKAN TELUR KUTU KEBUL (Bemisia tabaci Genn.) - Febi Wahyu Sulistyadi; Serafinah Indriyani; Suharjono Suharjono (Biotropika: Journal of Tropical Biology, 2013)
Groundnut crop which is widely used in various fields. However, there are some pests that attack peanuts, one of which is the whitefly pest that lays eggs on the leaves. Laying eggs on the leaves can cause some damage. This study aimed to determine the relationship of density and length of the peanut leaf trichomes against whitefly infestation preference laying eggs on the leaves of peanuts. The method used is to plant 16 varieties of groundnut in the usual places visited by whitefly infestation. After the age of groundnuts ± 1.5 months taken leaf samples of peanut varieties, each variety was taken three leaves as replicates. Further microscopic preparations were made for length and density of trichomes observed on the abaxial whitefly infestation and the number of eggs in each sample and leaf damage observed macroscopically. Data analysis was done by correlation test number nits whitefly trichome length and density with SPSS 16 for Windows as well as analysis and cause leaf damage. Based on the research and observations that have been made can be seen that there is a positive and highly significant correlation between the density of leaf trichomes peanut and egg laying whitefly infestation in peanut leaves by Pearson correlation values ​​respectively of 0.86 at 0.01 level. While long relationship peanut leaf trichomes and laying eggs on the leaf whitefly infestation peanuts have a positive and significant correlation based on the value of 0.597 at 0.05 level. Thus it is known that whitefly infestation happy laying eggs on the leaves of peanuts with a tight and long trichomes.